Jewish women in Europe in the Middle Ages : a quiet revolution - Goldin, Simha (Gender in history., 2020)
Goldin's study explores the relationships between men and women within Jewish society living in Germany, northern France and England among the Christian population over a period of some 350 years. Looking at original Hebrew sources to conduct a social analysis, he takes us from the middle of the tenth century until the middle of the second half of the fourteenth century, when the Christian population had expelled the Jews from almost all of the places they were living. Particularly fascinating are the attitudes towards women, as well as their changes in social status. By examining the factors involved in these issues, including views of the leadership, economic influences, internal power politics and gender struggles, Goldin's book provides a greater understanding of the functioning of these communities. This volume will be of great interest to historians of medieval Europe, gender and religion.